A Prospective Study to Evaluate the Efficacy of Botulinum Toxin-A in the Management of Dysfunctional Voiding in Women. (November 2018) - Krishnappa, Pramod; Sinha, Maneesh; Krishnamoorthy, Venkatesh
Objectives: To assess the outcomes of Botulinum Toxin-A (BoNT-A) to the external urethral sphincter (EUS) in dysfunctional voiding (DV) refractory to standard urotherapy and bowel management. Methods: Our criteria to diagnose DV in women included neurologically normal individuals with lower urinary tract symptoms, dilated proximal urethra on voiding cystourethrogram, and high detrusor pressure (PdetQmax > 20 cm H2 O) associated with increased electromyography activity during voiding in urodynamic study (UDS). A total of 16 female patients with a median age of 36 years (5-60 years) received BoNT-A from June 2014 to December 2015. Patients below and above 10 years of age received 100 units and 200 units of BoNT-A to EUS, respectively. Patients were followed up till 6 months. Results: Mean AUA (American Urological Association) symptom score decreased significantly from 11.75 ± 6.14 to 5.06 ± 5.1 and 4.25 ± 3.4 at day 14 and day 45 after BoNT-A, respectively ( P < .0001). There were no significant improvements in maximal flow (Qmax) on uroflowmetry (UFM) and detrusor pressure at maximal flow (PdetQmax) in UDS. Significant reduction in post-void residual (PVR) from 69.31 ± 77.3 to 17.50 ± 22.3 mL at day 14 ( P = .007) was observed, although the reduction was not significant at day 45. Although minor adverse effects were reported, none were serious or life-threatening. Conclusions: Our study showed that BoNT-A plays a role in improvement of urinary symptoms and reduces PVR at D14 in DV, but showed no improvement in UFM and urodynamic parameters, albeit with limited numbers and limited follow-up.